Emerging roles of metabolic biomarkers in renal cell carcinoma: from molecular mechanisms to clinical implications - Yang, Junkai; Miao, Daojia; Li, Xinwei; Zhao, Chuanyi; Tan, Diaoyi; Wu, Songming; Lu, Feiyi; Shi, Jian; Lv, Qingyang; Ruan, Hailong; Xiong, Zhiyong; Zhang, Xiaoping (Frontiers in Cell and Developmental Biology, 2025)
Renal cell carcinoma (RCC) is a common malignancy of the urinary system. Due to its asymptomatic nature in the early stages, many patients present with advanced or metastatic disease at the time of diagnosis. Existing therapeutic strategies for advanced RCC exhibit limited efficacy, underscoring the urgent need for novel therapeutic approaches. Recently, metabolic reprogramming—characterized by alterations in glucose metabolism, lipid synthesis, and amino acid metabolism—has emerged as a critical biological adaptation enabling tumor cell proliferation and survival within the tumor microenvironment. This review introduces the major metabolic reprogramming mechanisms in RCC, including enhanced glycolysis, augmented lipid synthesis, and altered amino acid metabolism. We summarize the associations between RCC progression and key metabolic molecules involved in these pathways, highlighting their potential clinical value as diagnostic markers, prognostic indicators, and therapeutic targets. To date, most studies have focused primarily on describing the correlations between metabolic dysregulation and tumor progression or therapeutic resistance in RCC. However, the molecules and pathways involved in these metabolic processes also represent promising targets for metabolic interventions. In this context, we further propose novel therapeutic strategies targeting key metabolic nodes such as HIF-2α, GLUT and FASN, offering new insights into precision treatment approaches for RCC.